Biopsychosocial Determinants of Pregnant Women’s Behaviour in Conducting Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome (HIV/AIDS) Tests in Madiun - Wida Rahma Arwiyantasari; Supriyadi Hari Respati; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: Human Immunodeficiency Virus (HIV) is top ranked infectious disease which causes death with high mortality and morbidity rates, and requires diagnosis and long-term therapy (WHO, 2013). In October 2016, Health Office of Madiun City stated that in 2015, there were 2,772 pregnant women, among those only 1,120 conducted HIV-AIDS tests and 4 of them declared HIV positive. These numbers indicated that the participations of pregnant women in conducting HIV-AIDS tests are not optimal. This study aimed to discover biopsychosocial determinants in conducting HIV-AIDS tests on pregnant women in Madiun.Subject and Methods: This was an analytic observational study with case control design. A total of 108 samples of pregnant women in Madiun which consisted of 54 pregnant women who conducted HIV/AIDS tests as cases, and 54 pregnant women who did not conduct HIV/ AIDS tests as controls were collected by using fixed disease sampling The device to gather the data was a set of questionnaire. Data analysis used Chi Square and path analysis.Results: There were positive influence of family support (b=1.57; 95% CI= 0.52 to 2.63; p=0.004), information exposure (b=1.14; 95% CI= 0.33 to 1.95; p=0.006), perceived seriousness (b=1.21; 95% CI= 0.14 to 2.28; p=0.027), perceived vulnerability b=1.12; 95% CI= 0.12 to 2.13; p=0.028), perceived benefit (b=1.28; 95% CI= 0.23 to 2.31; p=0.017) on pregnant women’s behaviour in conducting HIV/ AIDS tests, and statistically significant. There were negative influence of family income (b=-0.73; 95% CI= -1.51 to 0.05; p=0.067), perceived obstacles (b=-0.92; 95% CI= -1.99 to 0.15; p=0.093) and statistically significant.Conclusion: Family support, information exposure, family income, perceived seriousness, perceived vulnerability, perceived obstacles, and perceived benefit influence pregnant women in conducting HIV/ AIDS tests.Keywords: determinants, bipsychosocial, HIV/ AIDS testCorrespondence: Wida Rahma Arwiyantasari. Muhammadiyah Midwifery Academy Madiun. Email: widarahmaarwiyantasari@ymail.com. Mobile: 085736709597.Journal of Health Promotion and Behavior (2017), 2(2): 112-123https://doi.org/10.26911/thejhpb.2017.02.02.02